2003
DOI: 10.1677/jme.0.0310021
|View full text |Cite
|
Sign up to set email alerts
|

CTLA-4 and its role in autoimmune thyroid disease

Abstract: Autoimmune thyroid disease (AITD) occurs in two common forms: Graves' disease and Hashimoto thyroiditis. On the basis of functional and experimental data, it has been suggested that the gene encoding cytotoxic T-lymphocyte-associated antigen-4 (CTLA-4) is a candidate gene for conferring susceptibility to thyroid autoimmunity. In this review, we critically evaluate the evidence for pathogenetic involvement of CTLA-4 in the various forms of AITD and focus on the possible role of genetic variation of the CTLA4 lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
86
2
5

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(96 citation statements)
references
References 104 publications
3
86
2
5
Order By: Relevance
“…In the available literature, studies on the polymorphism of CTLA4 exon1 A49G have shown conflicting results. Indeed, some studies disagree with our findings and suggest significant associations with GD and HT for both 49A/G and CT60G/A (Chistiakov and Turakulov 2003;Kavvoura et al 2007;Furugaki et al 2004) while others suggest that CTLA4 leads to the production of thyroid autoantibodies but it does not contribute to AITD (Tomer et al 2001).…”
Section: Discussioncontrasting
confidence: 81%
“…In the available literature, studies on the polymorphism of CTLA4 exon1 A49G have shown conflicting results. Indeed, some studies disagree with our findings and suggest significant associations with GD and HT for both 49A/G and CT60G/A (Chistiakov and Turakulov 2003;Kavvoura et al 2007;Furugaki et al 2004) while others suggest that CTLA4 leads to the production of thyroid autoantibodies but it does not contribute to AITD (Tomer et al 2001).…”
Section: Discussioncontrasting
confidence: 81%
“…Those which are linked to reduced protein expression, such as À318C4T in the promoter and 49A4G in exon 1 of CTLA4, 5,6 have been associated with increased frequency of autoimmune diseases like Graves' disease, autoimmune hypothyroidism, type 1 diabetes and multiple sclerosis. [7][8][9] In the current study, we aimed to evaluate whether the low expression CTLA4 polymorphisms À318C4T and 49A4G were associated with the risk of developing AA and whether they were linked to a worse response to IS therapy.…”
Section: Discussionmentioning
confidence: 99%
“…19 Apart from CD, the 2q33 locus has been studied as a candidate susceptibility locus for autoimmune diseases such as type I diabetes 20 and autoimmune thyroid disease. 21 In addition, a large deletion affecting exons 2 and 3 of the ICOS gene has been described in four CVID patients from two families. 22 This 1815 bp deletion results in an mRNA frameshift with a premature stop codon, abolishing the expression of ICOS at the cell surface.…”
Section: Introductionmentioning
confidence: 99%